1980
DOI: 10.1128/aem.40.2.301-304.1980
|View full text |Cite
|
Sign up to set email alerts
|

Some Effects of Douglas Fir Terpenes on Certain Microorganisms

Abstract: The Douglas fir terpene α-pinene was shown to inhibit the growth of a variety of bacteria and a yeast. Other terpenes of the Douglas fir, including limonene, camphene, and isobornyl acetate, were also inhibitory to Bacillus thuringiensis . All terpenes were inhibitory at concentrations normally present in the fir needle diet of Douglas fir tussock moth larvae. The presence of such terpenes in the diet of these insects was found to strongly influence the infectivity of B. thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(73 citation statements)
references
References 14 publications
3
70
0
Order By: Relevance
“…The oil inhibited respiration in cell suspension and disrupted the permeability barrier of microbial membrane structures (COX et al 2000). In yeast cells and isolated mitochondria, α-pinene and β-pinene destroyed cellular integrity, inhibited respiration and ion transport processes and increased membrane permeability (ANDREWS et al 1980, URIBE et al 1985. The MIC of eugenol and thymol oils against S. cerevisiae was 1.8 and 1.5 mM while the minimum fungistatic concentrations (MFC) were 3.0 and 1.8 mM, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The oil inhibited respiration in cell suspension and disrupted the permeability barrier of microbial membrane structures (COX et al 2000). In yeast cells and isolated mitochondria, α-pinene and β-pinene destroyed cellular integrity, inhibited respiration and ion transport processes and increased membrane permeability (ANDREWS et al 1980, URIBE et al 1985. The MIC of eugenol and thymol oils against S. cerevisiae was 1.8 and 1.5 mM while the minimum fungistatic concentrations (MFC) were 3.0 and 1.8 mM, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…depressa stem extract (Sato et al, 2000;Nakanishi et al, 2004;Inatomi et al, 2005). Terpenes, lignans and coumarins have been shown to be active against a wide variety of microorganisms, including gram-positive and gram-negative bacteria and fungi (Andrews et al, 1980;Uribe et al, 1985;Cowan, 1999;Kawaguchi et al, 2009;Nakato et al, 2009;Widelski et al, 2009). These active compounds were detected in aerial parts of J. communis var.…”
Section: Resultsmentioning
confidence: 99%
“…The antimicrobial action of essential oils and their monoterpenoid components can be explained by their toxic effects on membrane structure and lethal effect on cellular functions. 15 Sikkema et al 28 showed that as a result of their lipophilic character, cyclic monoterpenes preferentially partition from an aqueous phase into membrane structures. This results in membrane expansion, increased membrane fluidity, and inhibition of membrane-embedded enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them, in particular D-limonene, inhibit the growth of bacteria, fungi, parasites, and cancer cells in vitro, whereas others suppress several enzymes. [14][15][16][17] Dead Sea magnesium salt is harvested from the waters of the Dead Sea. Magnesium chloride (MgCl 2 ) is obtained by further dehydration of this salt by heat and flaking/pelletizing processes.…”
mentioning
confidence: 99%